Income distribution: An important factor for economic forecasts - Ferdinand Fichtner; Simon Junker; Carsten Schwäbe (DIW Economic Bulletin, 2012)
The development of private consumption is a crucial factor in compiling macroeconomic projections as part of national accounts. Household savings also play an important role as an explanatory variable for consumer development, since private households must decide whether to spend their incomes on consumption or saving. The estimated savings rate in DIW Berlin's economic projections can be improved by including micro-data from the German Socio-Economic Panel Study (SOEP). It is evident that the significant increase in the savings rate in the years before the crisis in 2008/2009 is also related to the redistribution of income. While relatively low earners receive their income overwhelmingly from wages or social welfare benefits, wealthy households not only receive higher wages, but also earn the bulk of their money from entrepreneurial activities and income from investments. Particularly in the years before the financial crisis, the latter increased dramatically while wages remained virtually static. Strong income growth has therefore primarily benefited those segments of the population that save a lot. If wage and profit incomes had developed similarly, consumer demand in Germany would have grown faster. In the next two years, however, a further increase in the savings rate is unlikely because of rapidly rising wages.
Keywords: E21; E25; D31; D12; 330; private consumption; savings rate; income distribution; economic projections